A Cretaceous continental vertebrate fauna from the Precordillera of La Rioja, Argentina - Hechenleitner, Esteban Martín (2019)
The record of Cretaceous continental vertebrates of Northwest Argentina (NWA) is relatively scarce compared to Patagonia and southeastern Brazil. In La Rioja, almost all the tetrapod specimens come from Los Llanos Formation (Upper Cretaceous), in the foothills of Sierras Pampeanas. So far, the only exception in western areas was an isolated record of two caudal centra of a titanosaur sauropod unearthed at the Quebrada de Santo Domingo locality (Ciénaga del Río Huaco Formation, Maastrichtian?), in Precordillera. In 2015 we have started a project, which includes prospection and extraction of fossils at the Mesozoic red beds of this locality, with the aim of expanding the knowledge about the faunas that inhabited NWA. Here, we report the discovery of a faunal assemblage composed of saurischian dinosaurs and crocodyliforms. Among the first, titanosaur sauropods are the most frequent, with several specimens that belong (at least) to two new species, closely related to “Aeolosaurini”. In association with some of them, we recovered several teeth of abelisaurid theropods and possible peirosaurid crocodyliforms. In addition, we also identified a titanosaur nesting site recorded in several egg-bearing levels. These findings are important, in terms of quality and quantity of specimens, for the Province of La Rioja, as well as NWA. The significant paleolatitudinal distinction between the recent findings from La Rioja and the faunas from Patagonia and Brazil, plus the fact that large areas of southern South America were likely flooded by epicontinental seaways at the Late Cretaceous, offer an interesting opportunity to understand their paleobiogeographic relationships.